A BIOLOGICALLY MEANINGFUL PROBABILITY DESCRIPTION OF PLANKTON STOCKS - Anderson, James Jay; Sutomo, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
Plankton standing stocks can be described with a gamma probability distribution based on a stochastic logistic equation. The stock is characterized by a carrying capacity and a randomness coefficient.